Viability of E-Learning Approach in the University of Khyber Pakhtunkhwa - Ishtaiq Hussain, Nabi Bux Jumani, Maqsood Ahmed, Sarfraz Ahmad (PJDOL, 2023)
The present study was aimed to find out viability of e-learning approach in the universities of Khyber Pakhtunkhwa so that problems faced during implementing e-learning approach may be addressed. It was made possible through highlighting the five factors during a survey.